NEEDS ANALYSIS ON ENGLISH MACRO-SKILLS FOR THE TOURISM STUDENTS OF HIGHER EDUCATION - Weka Kusumastiti; Angesti Palupiningsih (Yavana Bhasha : Journal of English Language Education, 2021)
English as international language becomes the bridge between the guests and the host intourism activities. As the consequence, Indonesia as the country that popular with its tourism potentialshould prepare its human resource to support the tourism activity for its betterment. One of them ispreparing them with English Macro-skill. English macro-skills consist of 4 skills: Reading, Listening,Writing, and Speaking. This research is aiming at analyzing the needs of English Macro-skills for theTourism Students of Higher Education. Empirical data in this research were collected throughquestionnaire. The questionnaire was spread trough 100 tourism students of Ambarrukmo TourismInstitute Yogyakarta whose experience in doing internship period. The result found that one skill isabove important than the others, some found that all of them are important, or they should be taughtintegrated. As the findings show, based on the students’ internship experience and the students’perspective, those 4 English macro-skills are important but they have different frequency of use in thework place. Reading is the most frequently use since they often deal with short functional text, such asannouncements and notice. Then it was followed by listening, writing, and speaking.